Perubahan Konstitusi Melalui Perjanjian Internasional dan Dampaknya Terhadap Kedaulatan Negara - Khairul Fahmi (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
The development of the association of modern states increasingly influences how the constitutional norms of the country are guarded and maintained. Inter-state relations in the economic, social, political, and security sectors established through various treaties have influenced the existence of the constitution because of the impact on multiple changes. Furthermore, it also affects the integrity of the country's sovereignty, especially when there is a conflict between the international legal system and the constitution. In this connection, the problem discussed is how constitutional changes occur through international treaties and how the impact of constitutional changes through international conventions on the existence of state sovereignty placed in the hands of the people. This study concludes, Firstly, the 1945 Constitution as a constitution has not only changed through formal changes in accordance with Article 37 of the 1945 Constitution but has also been changed in an informal manner through the ratification of international treaties. Second, amending the constitution through international treaties can reduce the existence of the constitution as the embodiment of the country's supreme power, which is placed by the people.